Radical directed regioselective functionalization of diverse alkene derivatives. (24th October 2022) - Suresh, Pavithira; Prasanna Kumari, Subramaniyan; Krishna Reddy, Singarajanahalli Mundarinti; Anthony, Savarimuthu Philip; Thamotharan, Subbiah; Selva Ganesan, Subramaniapillai
Abstract : Regioselective vicinal difunctionalization of diverse alkene derivatives was successfully carried out using readily available carboxylic acids. Abstract : Regioselective vicinal difunctionalization of diverse alkene derivatives was successfully carried out using readily available carboxylic acids. Molecular oxygen in the atmospheric air tethered with the substrate to form the corresponding peroxygenated products in good yields. All the reactions were carried out at room temperature itself. Apart from the synthesis of peroxygenated products, hydroacylated products were obtained by utilizing Csp 2 hybridized carbonyl radicals instead of Csp 3 hybridized alkyl radicals.